2020
DOI: 10.1002/sce.21562
|View full text |Cite
|
Sign up to set email alerts
|

The effect of professional development on elementary science teachers’ understanding, confidence, and classroom implementation of reform‐based science instruction

Abstract: Through a randomized controlled trial, this mixed-methods study evaluated changes in elementary science teachers' understandings, confidence, and classroom implementation of problem-based learning (PBL), inquiry, and nature of science (NOS) instruction following participation in a professional development (PD) as well as the components of the PD that teachers perceived facilitated these changes. Results indicated that following the PD, treatment teacher (n = 139) understandings of and confidence for teaching i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…Results of the current study established that teachers self-efficacy affect 82.90% on implementing STEM education that supports the findings of Srikoom and Faikhamta (2018), who reported that teachers self-efficacy significantly effect on implementing STEM education. Selfefficacious teachers have more confidence in their cognitive abilities towards implementing STEM education (Maeng et al, 2020;Rahmadi et al, 2020). Results of current research congruent with the findings of the studies conducted in the USA (Wang et al, 2011), UK (Morgan & Kirby, 2016), Australia (Office of the Chief Scientist, 2013) and in Canada (DeCoito, 2016a), which reveals that teachers confident play an imperative role in implementing students potential towards implementing STEM education (Sanders, 2009).…”
Section: Research Resultssupporting
confidence: 84%
“…Results of the current study established that teachers self-efficacy affect 82.90% on implementing STEM education that supports the findings of Srikoom and Faikhamta (2018), who reported that teachers self-efficacy significantly effect on implementing STEM education. Selfefficacious teachers have more confidence in their cognitive abilities towards implementing STEM education (Maeng et al, 2020;Rahmadi et al, 2020). Results of current research congruent with the findings of the studies conducted in the USA (Wang et al, 2011), UK (Morgan & Kirby, 2016), Australia (Office of the Chief Scientist, 2013) and in Canada (DeCoito, 2016a), which reveals that teachers confident play an imperative role in implementing students potential towards implementing STEM education (Sanders, 2009).…”
Section: Research Resultssupporting
confidence: 84%
“…They also conceived science learning as reception of knowledge and manipulation of materials to practice activities demonstrated by the teacher. These findings are similar to findings prior to but differ from findings after professional developments and methods courses in other contexts (Choi & Ramsey, 2009;Crawford, 2007;Haefner & Zembal-Saul, 2004;Maeng et al, 2020). While the effectiveness of inquiry-based instruction is widely acknowledged and many countries are seeking to adopt and implement this pedagogical approach, the present findings and others (Dudu & Vhurumuku, 2020;Mokiwa & Nkopodi, 2014;Mugabo, 2012) suggest that there are preservice and in-service teachers in many contexts without or with little clues about the activities and thinking processes used to generate explanations for natural phenomena.. Empirical evidence also shows that many teachers in this study context, like teachers in similar contexts, have no or little clues about how to structure knowledge and create authentic learning environments that convey to students images of scientific practices resembling the work of actual scientists.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the comparisons and contexts in which the codes were used, each participant's responses about scientific inquiry, inquiry teaching, and inquiry learning were categorised either as traditional, partially informed, or fully informed conception (J. S. Lederman et al, 2014;Maeng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address the challenge, researchers have recommended the infusion of language and literacy into science instruction to support science learning (i.e., Llosa et al, 2016;Maerten-Rivera et al, 2016;Tong et al, 2014a;Tong et al, 2014b). Researchers have determined effective strategies integrating science and literacy to encourage teachers' use of scientific classroom discourse (e.g., Lewis et al, 2015), improve teachers' quality of instruction (e.g., Maeng et al, 2018), and increase teachers' understanding, confidence, and delivery of science-literacy integration instruction (e.g., Maeng et al, 2020;Santau, et al, 2010;Tong et al, 2019). Such integrated instruction has demonstrated positive evidence of enhancing students' learning in science (i.e., Llosa et al, 2016;Maerten-Rivera et al, 2016) or in both science and literacy (Lara-Alecio et al, 2012;Tong et al, 2014aTong et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%